(untitled) (Bangladesh Journal of Agricultural Research, 2016)
The study analyzed the trends, growth rates of area, production and yield of major fruits in Chittagong region and identified factors contributing to output growth during 1993/94-2009/10 using secondary data. The fruits under study were mango, jackfruit, litchi, guava, banana, papaya, ber, pomelo, pineapple, watermelon, lime and lemon. The study revealed that the area of all fruits increased over the period except banana, ber, pomelo and water melon. The highest increase in area was estimated for guava (131.6%) and the lowest for jackfruit (6.4%). Similarly, the production of all fruits over the period was increased except banana and pineapple. The average annual growth rates of area, production and yield for all fruits were found to be positive in all periods (i.e, period I: 1993/94-1997/98; Period II: 1998/99-2003/04, and Period III: 2004/05- 2009/10). But the magnitude of the growth rates of area for all fruits varied significantly. The growth rates of area for mango, jackfruit, litchi and pineapple were increased impressively and significantly. This might be due to the adoption of improved variety and management practices by the farmers. The growth rate of area, production and yield of banana decreased drastically over the period due to absence of modern variety of banana and lack of improved management practices in the region. The growth rates of production for mango were found to be highest in the period III (2004/05-2009/10). But the growth rate of yield of mango was found to be decreased significantly over the periods due to improper management against the pest and diseases by the farmers. The highest percentage of output changed was observed in Banana (149%) followed by pineapple (106%) and jackfruit (83%) between the periods. The lowest percentage of output changed was found in guava (11.7%). The contribution of area was the highest in changing output for mango, jackfruit, litchi, guava, ber, pomelo, watermelon, lime and lemon. The contribution of yield was the highest for banana (135.57%), papaya (76.92%) and pineapple (158.62%) for changing output indicated that the increased area was more responsible for changing in output growth of selected fruits. To increase the growth rate of fruits, improved variety and management practices should be disseminated through undertaking special programme and strengthening research-extension linkage in the Chittagong region. Bangladesh J. Agril. Res. 41(1): 137-150, March 2016